From Marvel scenes to speech delivery rates: A TBLT model for Pesantren-based EFL listening enhancement - Aries Fachriza; Ervina Rahma Neysa; Ana Maghfiroh; Tintin Susilowati (Journal on English as a Foreign Language, 2026)
Although films and task-based language teaching (TBLT) have been widely applied in EFL listening instruction, their combined use to examine speech delivery rates (SDRs) outcomes, particularly in Pesantren-based educational settings, remains underexplored.  This study seeks to investigate the effectiveness of Marvel movie scenes in enhancing SDRs in listening among EFL students in a Pesantren context. A quasi-experimental quantitative study involved two groups of 74 students from a private Islamic boarding school in East Java, Indonesia. Both groups were exposed to the same Marvel movie. The experimental group was taught using TBLT with communicative tasks, while the control group received conventional instruction. An independent samples t-test was applied to determine differences between the groups, and a paired samples t-test examined retention after a two-week interval. Results showed that the TBLT group outperformed the non-TBLT group by 8.35 points, with Sig. value 0.001 in both comprehension and retention. The TBLT group indicated stronger retention of SDR features. Retention scores differed significantly between the TBLT and non-TBLT groups, t = 3.48, p < .001, SE = 7.11.  These findings imply that EFL teachers can adopt TBLT-supported authentic film media to enhance SDR-focused listening, significantly improving listening skills and long-term memory retention among Pesantren students in practice.